2012
DOI: 10.1002/j.1532-2149.2012.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy attenuates neuropathic hyperalgesia in rats and idiopathic trigeminal neuralgia in patients

Abstract: Background: Neuropathic pain after nerve injury is severe and intractable, and current drug and non-drug therapies offer very limited pain relief. Hyperbaric oxygen (HBO2) has been clinically used for protection of the nervous system after acute injury. We investigated whether HBO2 treatment could prevent and/or attenuate neuropathic pain in animals and in patients. Methods: Mechanical allodynia and thermal hyperalgesia and neurochemical alterations of neuropathic pain were analysed in male, adult, Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 38 publications
(61 reference statements)
2
51
0
Order By: Relevance
“…While 1 h treatment did not reach significant difference compared with treatment with air. Gu et al 13 reported that treatment with pure oxygen for 70 min for seven consecutive days did not significantly alter the increased thermal sensitivity in neuropathic rats. This result was accordance with ours in SCI patients with neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While 1 h treatment did not reach significant difference compared with treatment with air. Gu et al 13 reported that treatment with pure oxygen for 70 min for seven consecutive days did not significantly alter the increased thermal sensitivity in neuropathic rats. This result was accordance with ours in SCI patients with neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…On the GPIC results, 4h per day InHO produced analgesic effect in 42.9% patients, which was o1h hyperbaric oxygen treatment (60-75%). 13 To assess some aspect of quality of life scales, SF-36ww and PGIC were used. Significant difference was found only at day 14 in SF-36ww pain scores and PGIC results, which was accordance with the result of VAS scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations